Analysis of Transportation Mode Choice for Electric Rail Train (KRL) and Bus For Yogyakarta-Surakarta Travel Routes - Permana Santoso, Gilang; Dwiatmoko, Hermanto (Universitas Ibn Khaldun Bogor, 2023)
The presence of the electric rail train (KRL) on the Yogyakarta-Surakarta route expands the list of public transportation modes available to residents of Yogyakarta, Surakarta, and surrounding areas. The Yogyakarta-Surakarta route was previously served by one of the road-based transportation, namely Bus, which was widely used but was abandoned by its users due to a variety of factors. The presence of various alternative modes of transportation today, combined with the Covid-19 pandemic, allows users of public transportation services, particularly the Yogyakarta-Surakarta route, to freely make their choices. Data was gathered through direct interviews and online questionnaires distributed using Google forms. Multiple linear regression and binary logit nisbah were used in the data analysis, and the results were obtained using software, specifically Microsoft Excel and Statistical Product and Service Solutions (SPSS). The Study by binary logit results show that lowering the CBUS (Bus fee) by 1,58 times the unit of money from the CKRL (KRL fee) to Rp7.595/trip from the original Rp12.000/trip will increase bus users by 30%. If TBUS (bus time) is accelerated by 1,81 times the unit time from TKRL (KRL time) to 1 hour and 23 minutes/trip from the original 2 hours and 12 minutes, bus users increase by 50%. Bus users will increase by 70% while KRL users will decrease by 30%, so the number of FBUS (bus frequency) must be increased to 16 times/day from the original 10 times/day by 1,69 times FKRL (KRL frequency).